An historical record for the distribution of Euphractus sexcinctus (Xenarthra, Cingulata, Dasypodidae) in Argentina - Sánchez, Tatiana (2015)
The early distribution of Euphractus sexcinctus in central-southwestern Argentina is here confirmed through an historical record from La Rioja province that was found at the Buenos Aires “Museo Argentino de Ciencias Naturales Bernardino Rivadavia”, and neglected since 1935. The specimen corresponds to a complete head, with skull included, preserved in alcohol, collected by Dr. Salvador Mazza.